The Use of Business Model Canvas to Formulate Business Model on Game Online Store "Asuna Store" - Puspayuda, Ariya Tetuka; Jang Jaya, Rico Saktiawan (JURNAL ILMU MANAJEMEN, 2021)
This study is aimed to formulate the business model of Asuna Store using canvas model business. Currently, the phenomenon of online games has been greatly popular in Indonesia. This phenomenon encourages entrepreneurs to establish online game business. Asuna Store is aware of this online game business opportunity. Asuna Store is an Online Game Store operating in Yogyakarta since 2017. The services offered by Asuna Store include the sales of game items, rank jockey services, and tournament. The research method used in this research is descriptive method with a case study approach. The object of the case study in this research is the Asuna store. The sampling technique used to determine the respondents in this study was a non-probability sampling technique, namely purposive sampling.The object of this case study is Asuna Store. The primary data is taken through deep interview.The easiest way to find business model is by using business model canvas. The use of business model canvas will make it easier to see how the replica of the business in Asuna Store is running. The values offered by Asuna Store is to give friendly services, fast responses, and stable and competitive prices for the convenience of consumers of Asuna Store. Asuna Store is an online game store so it does not need physical store. The use of online information media such as Instagram, Snapgram, and Line Official really helps in the business operational of Asuna Store